2002
DOI: 10.1007/s00253-002-1183-5
|View full text |Cite
|
Sign up to set email alerts
|

Polyene antibiotic biosynthesis gene clusters

Abstract: Over the past 15 years the biosynthetic gene clusters for numerous bioactive polyketides have been intensively studied and recently this work has been extended to the antifungal polyene macrolides. These compounds consist of large macrolactone rings that have a characteristic series of conjugated double bonds, as well as an exocyclic carboxyl group and an unusual mycosamine sugar. The biosynthetic gene clusters for nystatin, pimaricin, amphotericin and candicidin have been investigated in detail. These cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
102
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 39 publications
2
102
0
5
Order By: Relevance
“…However, its role in the export of NTM remains unclear. In S. natalensis, PimT is an amino acid exporter involved in secretion of the NTM inducer PI factor, which to date has only been found in this host (Aparicio et al, 2003). A DpimT mutant shows a 65 % decrease in NTM production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its role in the export of NTM remains unclear. In S. natalensis, PimT is an amino acid exporter involved in secretion of the NTM inducer PI factor, which to date has only been found in this host (Aparicio et al, 2003). A DpimT mutant shows a 65 % decrease in NTM production.…”
Section: Discussionmentioning
confidence: 99%
“…Homologues of these genes are also located in the biosynthetic gene clusters for nystatin and amphotericin, and all of these clusters are thought to have common evolutionary origins. The gene pimH, which is also absent from other polyene macrolide biosynthetic gene clusters (Aparicio et al, 2003), has been suggested to encode a putative efflux pump, functioning as an alternative transport system. However, its role in the export of NTM remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of synthetic methodologies have been developed to chemically characterize this unique class of natural products [1,2]. Recently, biosynthesis of polyene macrolides has been intensively studied to generate improved fungicidal agents through genetic manipulations [3,4]. Although more than 200 polyene macrolides have been identified, the stereochemistry of many has not been fully characterized largely because of the signal overlapping in the NMR spectra due to the iterative structural motifs and structural complexity.…”
mentioning
confidence: 99%
“…Many Streptomyces species and some rare actinomycetes have the ability to produce a class of antifungal compounds, the polyene macrolides (Martín, 1977), that belong to the polyketide family (Omura & Tanaka, 1984;Aparicio et al, 2004). In recent years, clusters of genes encoding enzymes for the biosynthesis of a few polyene macrolides have been reported (Aparicio et al, 1999(Aparicio et al, , 2000(Aparicio et al, , 2003Brautaset et al, 2000;Caffrey et al, 2001). …”
Section: Introductionmentioning
confidence: 99%